A Tandem of Rare Complications Due to Stent Infection - Botchorishvili, Inga; Kipiani, Vakhtang; Agladze, Rusudan; Gaprindashvili, Tamar; Khajalia, Sergo; Pagava, Zurab; Vashakidze, Levan; Natsvlishvili, Vasil (Journal of Clinical Case Reports and Images, 2023)
This report details sequential rare complications arising from a vascular stent infection. Clinical course, microbiology, and imaging are outlined, with emphasis on early recognition and multidisciplinary management. Lessons for device surveillance and antimicrobial stewardship are highlighted.
Keywords: nosocomial infections; coronary wall injury; mortality